Student interaction in electronic environment - Banek Zorica, Mihaela (Array, 2011)
Faced with the new challenges of social software and web 2.0 tools, a question of implementing these in educational environment is raised. In order to better understand the information behaviour of students research was conducted on two academic institutions, state funded Faculty of Humanities and Social Sciences, University of Zagreb, and privately funded Accredited College of Business and Management Baltazar Adam Krčelić. Research was based on student information behaviour specifically on their patterns in using new web services (i.e. web 2.0 tools) and discovering new information needed in educational process. In order to recognize the need of implementing web 2.0 services in existing elearning systems, the patterns of their usage needed to be examined.